The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis